Enabling security in software-defined wireless sensor networks for internet of things - M. G. de Toledo, Cézar; A. G. de Oliveira, Doriedson; A. Simplicio Jr, Marcos; B. Margi, Cintia (Anais da Escola Regional de Redes de Computadores (ERRC), 2020)
In Software-Defined Wireless Sensor Networks (SDWSN), a logically centralized controller manages data ﬂows according to high level policies. As a result, it provides Wireless Sensor Networks (WSN) with further ﬂexibility and control over its nodes’ behavior. One challenge in this scenario, though, is that SDWSN are mainly composed of resource-constrained devices, which hinders the application of traditional cryptographic protocols in such networks. In this article, we propose a secure framework for SDWSN that takes into account such constraints, enabling the establishment of end-to-end security among nodes and between nodes and the SDN controller. Besides showing how our proposal can enforce different security services in an SDWSN, we also simulate our framework and present a preliminary security cost of framework.